Brief sea‐level fall event and centennial to millennial sea‐level variations during Marine Isotope Stage 19 in Osaka Bay, Japan. (27th October 2016) - Maegakiuchi, Kenta; Hyodo, Masayuki; Kitaba, Ikuko; Hirose, Kotaro; Katoh, Shigehiro; Sato, Hiroshi
ABSTRACT: Detailed sea‐level variation was investigated for Marine Isotope Stage (MIS) 19, based on diatom and grain size analyses of a marine sequence in a core of the Osaka Group. Diatom sea‐level proxies represent precession‐related signals correlated with highstands MIS 19.3 and 19.1, and lowstand MIS 19.2. Astronomical tuning shows the marine sequence has a uniform accumulation rate of about 60 cm ka −1 . A rapid sea‐level fall event was found in the earliest MIS 19, demonstrated by several independent sea‐level proxies of diatom and grain size. This event began with a rapid sea‐level drop, followed by a gradual recovery, at about 783–782 ka. A maximum abundance of pelagic diatom taxa at a core depth of 402.20 m evidently shows the highest sea‐level peak in MIS 19, supported by many other proxies. Based on the diatom data, sea‐level change across MIS 19.1 is characterized by centennial to millennial fluctuations. The sea‐level fall event began just after the onset of a cooling event previously reported from the same core. Observations of a comparable sea‐level fall signal in many deep‐sea core records suggest the event is global.